Strategic Decision Support for Urban Service Design. Issue 1 (1st March 2019) - Öz, Necmiye Yaprak; Demirkan, Halime
Abstract : The aim of the study is to propose an ontology-based approach that provides a framework as a strategy decision tool for urban service design. The research methodology includes two phases to acquire the knowledge needed for urban service management of a city, as a case study. The first phase provides the priority list, through the Principal Component Analysis, for an age-friendly city determined by the citizens through a quantitative research. The second phase is a qualitative research among the public service providers, focusing on 'adequate community support and health services' feature which was the top priority of phase one. The repertory grid as a mapping tool consists of elements (age-friendly cities' features) and constructs (municipality provided services) that interconnect the tacit knowledge with the external knowledge. The findings indicated the importance of the necessity of a shared understanding and conceptualization of what a service is among service providers and consumers. This paper makes an important contribution to urban service management by making the interconnection between tacit and external knowledge as a strategic decision support tool.